ANTIHYPERLIPIDEMIC EFFECT OF KOMOOTHIRA SILASATHU PARPAM IN TRITON-INDUCED ANTI DYSLIPIDEMIC RATS - P, Revathy; G, Thirunarayanan; P, Suvedha (Journal of Global Pharma Technology, 2024)
Background: Cardiovascular disease (CVD) is known to be associated with hyperlipidemia. The statin medicine class inhibits a stage that limits the production of cholesterol at a certain pace, although all statins have negative effects on the musculoskeletal system. The current interest has led to a hunt for novel lipid-lowering drugs with little to no side effects among traditional sources of siddha. Objective: The primary goal of this study is to assess the siddha formulation Komoothira silasathu parpam (KSP)’s antityperlipidemic capability in triton-induced dyslipidemic rats. Methods: Triton was used for the induction of hyperlipidemia in the experimental animals. The animals were divided into control, disease control and treatment groups. Rats belongs to treatment groups were administered test drug KSP at doses of 250 and 500 mg/kg/p.o. Results: The data of the present investigation clearly emphasise that the body weight, total cholesterol, HDL, LDL, VLDL, and triglyceride levels of the triton group demonstrate a significant increase in comparison with normal control rats. Treatment with the siddha formulation KSP at 250 and 500 mg/kg doses results in a significant decrease in the total lipid profile and body weight of the experimental animals, Furthermore, the KSP treatment causes a Consistent decrease in the internal organ weight (heart and liver) of the animals. Histological examination of the liver sample confirms the existence of inflammatory changes in triton treatment, and treatment with PVC reveals a restorative nature in both the dose level. Conclusion: In conclusion, the data of the present study show that the siddha formulation KSP reveals promising antihyperlipidemic activity in Triton induced dyslipidemic rats. Hence KSP type formulations may be the good drug of choice in the clinical management of hyperlipidemia Keywords: Hyperlipidemia, Siddha, Komoothira silasathu parpam, Lipid profile, Body weight, Histopathology.